Plp1 in the enteric nervous system is preferentially expressed during early postnatal development in mouse as DM20, whose expression appears reliant on an intronic enhancer - Patyal, Pankaj; Fil, Daniel; Wight, Patricia A. (Frontiers in Cellular Neuroscience, 2023)
Recently, the myelin proteolipid protein gene (Plp1) was shown to be expressed in the glia of the enteric nervous system (ENS) in mouse. However, beyond this, not much is known about its expression in the intestine. To address this matter, we investigated Plp1 expression at the mRNA and protein levels in the intestine of mice at different ages (postnatal days 2, 9, 21, and 88). In this study, we show that Plp1 expression preferentially occurs during early postnatal development, primarily as the DM20 isoform. Western blot analysis indicated that DM20 migrated according to its formula weight when isolated from the intestine. However, mobilities of both PLP and DM20 were faster than expected when procured from the brain. The 6.2hPLP(+)Z/FL transgene, which uses the first half of the human PLP1 gene to drive expression of a lacZ reporter gene, recapitulated the developmental pattern observed with the native gene in the intestine, indicating that it can be used as a proxy for Plp1 gene expression. As such, the relative levels of β-galactosidase (β-gal) activity emanating from the 6.2hPLP(+)Z/FL transgene suggest that Plp1 expression is highest in the duodenum, and decreases successively along the segments, toward the colon. Moreover, removal of the wmN1 enhancer region from the transgene (located within Plp1 intron 1) resulted in a dramatic reduction in both transgene mRNA levels and β-gal activity in the intestine, throughout development, suggesting that this region contains a regulatory element crucial for Plp1 expression. This is consistent with earlier studies in both the central and peripheral nervous systems, indicating that it may be a common (if not universal) means by which Plp1 gene expression is governed.